2020
DOI: 10.12659/msm.920736
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Transforming Growth Factor-β1 (TGF-β1) Signaling Pathway on Cell Proliferation and Cell Migration are Mediated by Ubiquitin Specific Protease 4 (USP4) in Hypertrophic Scar Tissue and Primary Fibroblast Cultures

Abstract: Background:Hypertrophic scar results from an abnormal repair response to trauma in the skin and involves fibroblasts proliferation with increased collagen deposition. Transforming growth factor-b1 (TGF-b1) and TGF-b receptor type I (TGF-bR1) are involved in tissue repair and are increased by ubiquitin-specific protease 4 (USP4). This study aimed to investigate the effects of TGF-bR1 and USP4 in human tissue samples of hypertrophic scar and on cell proliferation and cell migration in primary fibroblast cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Given that TGF-β1 is the predominant cytokine that stimulates the differentiation of lung fibroblasts into myofibroblasts and induces ECM production ( Sapudom et al, 2015 ; Huang et al, 2020 ), we examined the effect of anlotinib (the chemical structure is shown in Supplementary Figure S1 ) on TGF-β1-induced activation of primary mouse lung fibroblasts (MLFs). The CCK-8 assay results showed that anlotinib did not cause significant cytotoxicity at doses of 1 µM ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that TGF-β1 is the predominant cytokine that stimulates the differentiation of lung fibroblasts into myofibroblasts and induces ECM production ( Sapudom et al, 2015 ; Huang et al, 2020 ), we examined the effect of anlotinib (the chemical structure is shown in Supplementary Figure S1 ) on TGF-β1-induced activation of primary mouse lung fibroblasts (MLFs). The CCK-8 assay results showed that anlotinib did not cause significant cytotoxicity at doses of 1 µM ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Immunofluorescence analysis of α-SMA and fibronectin showed similar results ( Figures 1D,E ). We also examined whether anlotinib affected the proliferation and migration of fibroblasts, which have been shown to significantly contribute to many fibrotic pathologies ( Jarman et al, 2014 ; Huang et al, 2020 ). As shown by the EdU ( Figures 1F,G ) and CCK-8 results ( Figure 1H ), anlotinib treatment prevented the TGF-β1-induced proliferation of primary MLFs.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that the pathophysiology of keloids is due to prolonged proliferation and delayed remodeling [ 33 , 34 ] and is caused by an excessive accumulation of ECM [ 3 ]. Importantly, it is revealed by the dysregulation of the signaling pathway by TGF-β [ 8 , 35 , 36 , 37 ], as a proinflammatory cytokine. Evidence to date suggests that inflammation triggers the subsequent immune response cascade and that ILs are associated with keloid formation [ 9 , 10 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It inhibits the growth of fibroblasts and reduces endothelial budding and synthesis of procollagen and glycosaminoglycan. Also, it enhances the degeneration of collagen and fibroblasts (26) and triggers a significant decrease in VEGF, α-1-antitrypsin, and α-2-macroglobulin levels (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%